Graphene composite material and method for producing same
Patent Information
- Application Number
- JP2023535358
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-12-09
- Filing Date
- 2021-12-09
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2041-12-09
AI Technical Summary
Existing graphene composites, particularly those with Bernal stacked layers, face challenges in performance enhancement due to high layer numbers, low 2D/G ratio, and impaired interactions with other materials, necessitating higher graphene concentrations and reduced economic viability.
The use of turbostratic graphene, which has fewer layers and higher 2D/G ratio, is incorporated into rubber composites through methods like Joule heating and chemical-mechanical processing, allowing for improved dispersion and interaction with rubber matrices.
Turbostratic graphene composites exhibit enhanced mechanical, electrical, and thermal properties, enabling better performance with lower graphene concentrations and improved dispersion, making them suitable for various applications.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] SUMMARY OF THE DISCLOSURE
[0002] Embodiments disclosed herein relate to composite materials, particularly compositions and methods for making graphene composite materials. [Background technology]
[0002] Rubber composites can be used in a variety of applications. The properties of rubber can be improved by incorporating additional materials such as graphene into the polymer. Physical or chemical treatment of graphene or graphene oxide can be used to produce graphene / rubber composites with advantageous properties. Physical methods of producing graphene can include exfoliation, grinding, milling, and sonication of graphite in a suitable solvent. Chemical methods of producing graphene can include chemical oxidation / intercalation of graphite, exfoliation of graphite oxide by sonication, and chemical reduction of exfoliated graphene oxide to reduced graphene oxide. Exfoliation or reduction by chemical means can also be performed by rapid heating using microwaves, furnaces, heat baths, and lasers. Other methods of producing graphene include chemical / physical vapor deposition and carbon nanotube opening.
[0003] Generally, graphene and graphene oxide processed by chemical / physical methods result in graphene with 15-30 or more Bernal stacked layers, low 2D / G ratios (e.g., typically less than 0.3), and carbon content of 90-95%. Bernal stacking of graphene results in layers that are difficult to exfoliate.
[0004] When such graphene is included in a composite, such as a graphene-rubber composite, the number of layers is relatively high (15-30), so the inner layers contribute to the mass of the composite, but may not readily bond with other components in the composite, such as polymers, and therefore do not contribute significantly to the material performance of the graphene-based composite. To counter this performance degradation, higher concentrations of graphene are required in such composites to produce useful graphene composites, resulting in uneconomical materials. Furthermore, the lower purity of the graphene means that interactions of graphene with other materials, such as graphene-polymer interactions, may be further impaired.
[0005] Therefore, there is a need for new methods of making new graphene composites, such as graphene rubber composites or other composites containing graphene, that overcome these shortcomings. Summary of the Invention
[0006] A method for producing a composite material is provided, the method including providing a first material comprising turbostratic graphene, providing a second material comprising rubber, mixing the first material and the second material, and producing a turbostratic graphene-rubber composite.
[0007] A turbostratic graphene rubber composite is provided that includes a first material that includes turbostratic graphene and a second material that includes rubber.
[0008] A method for producing a composite material is provided, the method including the steps of providing a first material including polyhedral graphene, providing a second material, mixing the first material and the second material, and producing a polyhedral graphene composite material.
[0009] The second material may include any one or more of rubber, cement, concrete, epoxy, coating, asphalt, plastic, polymer, polyurethane foam, glass ceramic, tire material, tire tread structure, tire tread material, or wood composite material.
[0010] A method for producing a composite material is provided, the method comprising the steps of providing a first material comprising turbostratic graphene, providing a second material comprising a rubber monomer material, mixing the first material with the second material, polymerizing the rubber monomer material, and converting the rubber monomer material into a rubber polymer to produce a turbostratic graphene-rubber composite material, wherein the rubber polymer physically or chemically interacts with the turbostratic graphene.
[0011] The method may further include synthesizing a rubber polymer on the graphene surface or on the turbostratic graphene.
[0012] The method may further include curing the turbostratic graphene rubber composite.
[0013] The method may further include mixing the turbostratic graphene rubber composite with another material before curing.
[0014] The curing process may be accelerated by the addition of either a crosslinking agent, an accelerator, or heat.
[0015] The crosslinking agent may include sulfur.
[0016] The turbostratic graphene rubber composite may be uncured.
[0017] The turbostratic graphene can be in dispersion or powder form.
[0018] The rubber may be a solid.
[0019] The rubber may be a liquid rubber material. The liquid rubber material may be dispersed in an organic solvent or solvent mixture.
[0020] The method may further include extracting the organic solvent to produce a solid turbostratic rubber composite.
[0021] The liquid rubber material may be emulsified in water.
[0022] Turbostratic graphene can contain 1 to 10 layers.
[0023] Turbostratic graphene can contain 10 to 100 layers.
[0024] Turbostratic graphene can contain more than 100 layers.
[0025] Turbostratic graphene can include flake or sheet graphene and polyhedral graphene.
[0026] The turbostratic graphene may include flakes or sheets of graphene.
[0027] Turbostratic graphene can have a lateral size between 2 nm and 100 μm.
[0028] Turbostratic graphene can include polyhedral graphene.
[0029] The polyhedral graphene may have a diameter between 3 nm and 200 nm.
[0030] The polyhedral graphene may include a plurality of walls, each of the plurality of walls including 2 to 100 layers.
[0031] The method may further include mixing the rubber with a turbostratic graphene-containing medium, the turbostratic graphene-containing medium comprising any one or more of an oil, an organic solvent, water, or a mixture of solvents.
[0032] The method may further comprise the step of adding a surfactant and / or a dispersant to improve dispersion of the turbostratic graphene in the turbostratic graphene-containing medium.
[0033] The method may further include adding a demulsifier to the turbostratic graphene latex mixture and further processing the mixture to obtain a solid turbostratic graphene rubber composite.
[0034] The method may further include the step of neutralizing the treatment by washing with water and drying in an oven.
[0035] The method may further include the steps of adding a crosslinking agent, placing or pouring the uncured mixture into a mold, and heat curing the mixture.
[0036] The method may further include providing any one or more of a crosslinker, an accelerator, an antioxidant, a filler, and an interfacial functionalizing agent to the turbostratic graphene rubber composite prior to curing.
[0037] The turbostratic graphene rubber composite may contain 0.01 to 50 parts by mass of turbostratic graphene per 100 parts by mass of rubber.
[0038] The turbostratic graphene rubber composite may include 1.25 parts by weight of turbostratic graphene per 100 parts by weight of rubber.
[0039] The step of mixing the first material with the second material may include mechanical stirring, sonication, or high shear mixing.
[0040] Turbostratic graphene can include heteroatoms that improve the mechanical performance of turbostratic graphene.
[0041] The heteroatoms may induce a non-uniform charge distribution across the turbostratic graphene surface to enhance graphene-filler and graphene-polymer interactions, or function as promoters or antioxidants.
[0042] The method according to any one of claims 1 to 32, wherein the method may further comprise the step of functionalizing the turbostratic graphene by one or more of mechanical milling, hydrothermal or solvothermal treatment, chemical or electrochemical treatment to tune the polarity of the turbostratic graphene.
[0043] Turbostratic graphene can be functionalized to improve its interaction with other fillers in rubber composites.
[0044] Turbostratic graphene can be functionalized to initiate polymerization reactions or promote or inhibit oxidation of rubber composites.
[0045] The rubber may include any one or more of natural rubber, natural rubber, synthetic rubber, rubber latex, rubber solution, solid rubber or solid solution.
[0046] The rubber may be a non-crosslinked polymer.
[0047] Turbostratic graphene can be produced from non-graphitic materials.
[0048] Turbostratic graphene can be produced by Joule heating of a carbon source.
[0049] The graphene rubber composites may be used in at least one of the groups including automobile tires, composites for automobile tires, parts of automobile tires, tires for other vehicles, O-rings, sealing materials, washers, membranes, belts, foam rubber, flooring, roofing, sports materials, footwear, adhesives, gaskets, hoses, and gloves.
[0050] The turbostratic graphene rubber composite can be a tire compound.
[0051] The turbostratic graphene rubber composite may be a rubber composition for a tire tread.
[0052] Turbostratic graphene can be partially oxidized to form graphene oxide.
[0053] Any one or more of fillers, accelerators, antioxidants / antiozonants, or processing additives may be added to the turbostratic graphene rubber composite to optimize the material properties of the turbostratic graphene rubber composite, where the fillers include any one or more of carbon black, ZnO, and SiO2, the accelerators include any one or more of N-cyclohexyl-2-benzothiazole sulfenamide (CBS), 2-mercaptobenzothiazole (MB), N-tert-butyl-benzothiazole sulfonamide (TBBS), and diphenyl guanidine (DPG), and the antioxidants and antiozonants include any one or more of 4010NA, Nochek 4729A, 6PPD, TMQ, and stearic acid.
[0054] Surfactants / dispersants may be used to improve the dispersion of turbostratic graphene in the rubber.
[0055] The turbostratic graphene may be modified with functional groups to improve the interfacial interaction between the turbostratic graphene and the rubber matrix, the functional groups including any one or more of oxygen, hydroxyl, carbonyl, carboxylic acid, ketone, ether, unsaturated carbon, silane, chlorine, bromine, and fluorine.
[0056] The surface of turbostratic graphene can be grafted with polymer chains, alkenes, or alkynes to crosslink the turbostratic graphene with rubber.
[0057] The uncured composite may be mixed with a suitable rubber including any one or more of styrene-butadiene rubber (SBR), polyisoprene, isoprene / isobutylene rubber, acrylonitrile / butadiene rubber, ethylene / propylene / diene rubber (EPDM), ethylene / propylene rubber (EPM), chlorosulfonated polyethylene (CSM), styrene copolymers, styrene block copolymers, and styrene / isoprene / styrene (SIS) rubber.
[0058] The uncured composite material may be mixed in an internal mixer, including a Banbury mixer, or an open mixer, including a two-roll mill.
[0059] The turbostratic graphene may be pre-dispersed in high viscosity oil to improve the dispersion of the graphene in the rubber.
[0060] Other aspects and features will become apparent to those skilled in the art from the following description of several exemplary embodiments. [Brief description of the drawings]
[0061] The accompanying drawings are intended to illustrate various examples of the articles, methods, and apparatus herein. [Figure 1] 1 is a flow chart illustrating a method for manufacturing a turbostratic graphene rubber composite according to one embodiment. [Figure 2A] TEM image of few-layer turbostratic graphene derived from wood-based biochar produced by Joule heating. [Figure 2B] TEM and SEAD images of three-layer turbostratic graphene from wood-based biochar produced by Joule heating. [Figure 2C] 1 is a TEM image of an exemplary chemically mechanically post-treated turbostratic graphene produced by Joule heating of metallurgical coke, according to one embodiment. [Diagram 3] FIG. 1 is a pair of high magnification TEM images of closed and open polyhedral morphology graphene from recycled tire carbon black, according to one embodiment. [Figure 4] 1 is a STEM image of a three-dimensional structure comprising sintered polyhedral graphene particles derived from recycled tire carbon black, according to one embodiment. [Diagram 5] 13A-13C are additional TEM images of polyhedral graphene derived from recycled tire carbon black, according to one embodiment. [Figure 6] 1A-1D are TEM and SAED images of polyhedral graphene from recycled tire carbon black showing evidence of turbostratic nature, according to one embodiment. [Figure 7] 1 is a TEM image of polyhedral graphene derived from high quality carbon black, according to one embodiment. [Figure 8] 1 is an image showing the stability of a metallurgical coke turbostratic graphene natural rubber latex dispersion, according to one embodiment. [Figure 9] FIG. 13 is an image of a control natural rubber and an uncured 0.75 phr metallurgical coke turbostratic graphene natural rubber composite made from dilution of a 1.5 phr (parts by weight per 100 parts by weight rubber) masterbatch, according to one embodiment. [Figure 10] FIG. 2 is a bar graph comparing the mechanical properties of natural rubber, conventional graphene-containing natural rubber (XG), and metallurgical coke-derived turbostratic graphene (TG)-containing natural rubber, according to one embodiment. [Figure 11] FIG. 1 is a bar graph comparing the thermal conductivity of natural rubber (NR), conventional graphene-containing natural rubber (XG), and metallurgical coke-derived turbostratic graphene (TG)-containing natural rubber, according to one embodiment. [Figure 12] 1 is an image showing the dispersion of metallurgical coke turbostratic graphene in oil, according to one embodiment. [Figure 13] FIG. 2 illustrates cure curves of three types of turbostratic graphene versus a control (no graphene) in a typical tire tread formulation, according to one embodiment. [Figure 14] FIG. 2 illustrates the Mooney viscosity of three turbostratic graphene rubber composites versus a control rubber (no graphene) in a typical tire tread formulation, according to one embodiment. [Figure 15] 1 is a bar graph comparing hardness of three turbostratic graphene rubber composites versus a control rubber (no graphene) in a typical tire tread formulation, according to an embodiment. [Figure 16] 1 is a bar graph comparing tensile strength of three turbostratic graphene rubber composites versus a control rubber (no graphene) in a typical tire tread formulation, according to an embodiment. [Figure 17] 1 is a bar graph comparing the modulus of three turbostratic graphene rubber composites versus a control rubber (no graphene) in a typical tire tread formulation, according to an embodiment. [Figure 18A]1 is a flow chart illustrating a method for making a turbostratic graphene rubber composite, according to one embodiment. [Figure 18B] 1 is a flow chart illustrating a method for making a turbostratic graphene rubber composite, according to one embodiment. [Figure 19] 1 is a flow chart illustrating a method for producing a polyhedral graphene composite material, according to one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0062] Various devices or processes are described below to provide examples of the claimed embodiments. The embodiments described below are not intended to limit the claimed embodiments, which may be directed to processes or devices different from those described below. The claimed embodiments are not limited to devices or processes having all the features of any one device or process described below, or to features common to multiple or all of the devices described below.
[0063] Graphene is a nanotube of nanotubes densely packed into a honeycomb crystal lattice. 2 It refers to a material that is a one-atom-thick planar sheet of bonded carbon atoms, and further contains an intact ring structure of carbon atoms and aromatic bonds across at least the majority of the internal sheets, and lacks significant oxidative modification of the carbon atoms. Graphene can be distinguished from graphene oxide in that it has fewer oxygen-containing groups such as OH, COOH, and epoxides. "Graphene monolayer" refers to graphene that is a single layer of graphene. "Few-layer graphene" refers to graphene that is 2-10 layers of graphene. "Multilayer graphene" refers to graphene that is 10-100 layers of graphene. "Graphene nanoplatelet" refers to graphene that is more than 100 layers of graphene.
[0064] "Turbostratic graphene" refers to graphene with little order between the graphene layers. Other terms that may be used include misoriented, twisted, rotated, rotational defect, and weakly bonded. The rotated stacking of turbostratic graphene helps relax the interlayer bonds and increases the interplanar spacing along the c-axis, thereby resulting in superior physical properties over competing graphene structures when compared on a similar mass basis. Small differences in the stacking direction of adjacent layers translate into important differences in product performance. An important performance advantage of turbostratic graphene is that the multi-layer graphene structure is prone to separating into a few individual graphene layers, and the graphene layers tend not to recombine. The turbostratic nature of graphene may be observed and confirmed by Raman spectroscopy, transmission electron microscopy (TEM), selected area electron diffraction (SAED), scanning transmission electron microscopy (STEM), atomic force microscopy (AFM), and X-ray diffraction (XRD) analysis.
[0065] Turbostratic graphene can be sheet-like or flake-like graphene. Sheet-like or flake-like turbostratic graphene can be few layers (less than 10 layers), or multilayer (10-100 layers), or nanoplatelets (more than 100 layers). The lateral size of sheet-like or flake-like graphene can be from 2 nm up to 100 μm. Graphene sheets can include single grains or multiple grains.
[0066] Methods for making rubber-graphene composites, graphene composites with materials other than rubber, and composites containing graphene, specifically turbostratic graphene and polyhedral turbostratic graphene, and rubber composites are provided. The use of turbostratic graphene in composites, such as turbostratic rubber composites, can result in composites with more favorable mechanical, electrical, thermal and chemical material properties than comparable non-composite materials, or composites containing non-turbostratic or conventional graphene, such as Bernal stacked graphene.
[0067] 1, a flow chart illustrating a method 100 of manufacturing a turbostratic graphene rubber composite is provided. The method 100 may include steps 102, 104, 106, and 108.
[0068] In step 102, a first material including turbostratic graphene is provided.
[0069] The turbostratic graphene provided in step 102 may be defined in this disclosure as described above.
[0070] Turbostratic graphene can be produced by methods such as resistive (ohmic) Joule heating of a carbon source. "Carbon source" generally refers to any carbon-based material that can be converted to graphene material, preferably turbostratic graphene. The carbon source can be in any form, including powder form, or compressed pill shape. Carbon sources can include natural raw materials, processed natural raw materials, synthetic carbon, carbon-containing waste, recycled or second generation materials. Additionally, carbon sources can include, but are not limited to, charcoal, coke, petroleum coke, recycled tires, recycled plastics, biochar, tire carbon black, carbon black, metallurgical coke, plastic ash, plastic powder, biomass / biomass waste, food waste, ground coffee, anthracite, charcoal, corn starch, pine bark, polyethylene microwax, wax, chemplex 690, cellulose, naphthenic oil, asphaltenes, gilsonite, and carbon nanotubes.
[0071] Flash Joule Heating synthesis methods and configurations thereof are described in WO 2020 / 051000 (Tour et al., International Publication Date March 12, 2020), the entire contents of which are incorporated herein by reference.
[0072] Methods for synthesizing graphene by Joule heating of carbon pills and their construction are described in International Application No. PCT / CA2020 / 051368 (Mancevski, International Filing Date: October 13, 2020), the entire contents of which are incorporated herein by reference.
[0073] Referring to Figure 2A, an example of turbostratic graphene produced by Joule heating treatment that can be used as turbostratic graphene of the present invention is shown. Figure 2A shows TEM images 2002 and 2004 of few-layer flake-like turbostratic graphene produced from wood-based biochar.
[0074] Referring to FIG. 2B, a TEM image 2102 and a SEAD image 2104 of three-layer turbostratic graphene produced from wood-based biochar by Joule heating treatment are shown.
[0075] The turbostratic graphene produced by Joule heating may be post-treated to reduce the lateral size and exfoliate the graphene into fewer or few layers of graphene. Post-treatments may include mechanical milling, hydrothermal or solvethermal treatments, chemical or electrochemical treatments, chemical-mechanical treatments, or any combination thereof. Mechanical milling may be performed in a ball mill, pin mill, classifier mill, jet mill, rod mill, attrition mill, media mill, or the like. Mechanical milling may be performed in the presence of dry powder or with a wet medium. The medium may be a solvent, e.g., water, alcohol, NMP, DMSO, or the like. Hydrothermal or solvethermal treatments are performed in an autoclave with water or other organic solvents. The pressure of the autoclave is typically controlled to 1-6 MPa by adjusting the temperature and the solvent. This autoclave pressure may be higher than when industrial scale or grade equipment is employed. Chemical treatments use chemicals to oxidize graphene (e.g., Hummers method) or to exfoliate graphene using intercalants. Typical intercalants include DMSO, DMF, hydrazine, hydroquinone, pyrene, anthraquinone, benzoquinone, or similar compounds. Electrochemical treatments use electrochemical oxidation treatments to exfoliate graphene. Chemical-mechanical treatments add one or more chemical intercalants or one or more exfoliatants to the mechanical treatment. Such treatments combine any of the above mechanical mill tool selections with any of the above chemical treatment selections.
[0076] Referring to FIG. 2C, TEM images 1502, 1504 of typical chemically mechanically post-treated turbostratic graphene produced from metallurgical coke by Joule heating are shown. The chemical mechanical process used to produce the graphene of images 1502, 1504 includes ball milling of the turbostratic graphene with a pyrene exfoliant. As depicted in images 1502, 1504, the turbostratic graphene includes a flake-like morphology. The turbostratic graphene of images 1502, 1504 has a lateral size of several hundred nm and a thickness of less than 10 graphene layers.
[0077] The amount of turbostratic graphene provided in step 102 can vary such that the turbostratic graphene concentration varies from 0.01 parts by weight per 100 parts by weight rubber (phr) to 50 phr.
[0078] The turbostratic graphene provided in step 102 may include, but is not limited to, powder form graphene, solid graphene, or fluid form graphene, where the graphene is dispersed or dissolved in a fluid medium.
[0079] In some examples of method 100, the turbostratic graphene provided in step 102 may include polyhedral graphene. Polyhedral graphene may be defined as a polyhedral form of turbostratic graphene. The polyhedral graphene is assembled with turbostratic graphene walls and hollow centers. The turbostratic graphene walls range from 2-3 layers up to several hundred layers. The polyhedral graphene has an overall diameter of 3-200 nm.
[0080] Prior to the present invention, polyhedral graphene had not been used to make graphene rubber composites or other graphene-based composites.
[0081] The use of polyhedral graphene can lead to turbostratic graphene rubber composites and other graphene-based composites with improved material properties in some instances.
[0082] Referring to FIG. 3, TEM images 1602, 1604 of polyhedral turbostratic graphene from recycled tire carbon black are shown. Individual grains of the sample show discontinuities, with some open areas visible inside the grains. The entire grain is composed of several sintered or interconnected walls, each with a side length of 20-50 nm. These walls are not separate, but interconnected to each other. The walls are composed of a few layers of stacked graphene (>10 layers). Electron diffraction measurements of this sample show turbostratic crystalline domains.
[0083] In some polyhedral turbostratic graphene morphologies, at least two turbostratic graphene polyhedral structures (closed or open) are fused together as one structure, and the fused structures form chain-like structures with a major length of 100 nm to several microns. These interconnected polyhedral frameworks build up a three-dimensional structure. These structures, shown in images 1702, 1704 of FIG. 4, are non-planar micrometer-long structures. The structures are non-continuous, and the structures are composed of interconnected polyhedral graphenes with diameters of 20 to 50 nm, each exhibiting a few layers of graphene (e.g., more than 10 layers).
[0084] 5, additional TEM images 1302, 1304 of turbostratic graphene polyhedrons from recycled tire carbon black are shown, with diameters ranging from 5-50 nm and walls containing 5-100 layers of turbostratic graphene.
[0085] Referring to FIG. 6, a TEM image 1902 and SAED measurements 1904 are shown. An example of polyhedral graphene produced from recycled tire carbon black was analyzed to detect evidence of turbostratification between the graphene sheets. Due to the morphology of the graphene sample (20-50 nm interconnected hollow carbon particles), it is difficult to detect electron diffraction corresponding to the flat areas of the sample. The following SAED measurements were taken on a portion of the sample where the flat areas were exposed. The SAED measurements revealed multiple circular and high contrast areas indicating the presence of small crystalline domains of randomly oriented flat areas, indicating turbostratification between the sheets.
[0086] 7, TEM images 1402, 1404 of polyhedral turbostratic graphene derived from high quality carbon black are shown, with the diameter of the polyhedral graphene being 10-50 nm and the walls containing 10-30 layers of turbostratic graphene.
[0087] In some embodiments, the turbostratic graphene morphology includes flake or sheet graphene structures and polyhedral graphene structures. This structure can be obtained by Joule heating of a mixed feed. The feed includes at least two morphologies, a first morphology that produces mainly sheet graphene and a second morphology that produces mainly polyhedral graphene. Examples of feedstocks that produce mainly sheet graphene are charcoal, coke, and petroleum coke, and examples of feedstocks that produce mainly polyhedral graphene are recycled tire carbon black, carbon black, and plastic ash.
[0088] In some embodiments, the oil absorption coefficient (OAN) of polyhedral graphene can be controlled to match a specific rubber composite application. It is known that the OAN of the feed carbon black affects the performance of rubber composites made from such feedstock. The OAN of graphene can have the same effect on the performance of graphene-rubber composites. One way to control the OAN of polyhedral graphene structures is to use a feed with a desired OAN number and use flash Joule heating to convert it to graphene. Another control method is to increase the energy dose of Joule flash heating of the feed to increase the structural complexity (e.g., OAN) of the graphene.
[0089] In some cases, the turbostratic graphene can be partially oxidized to graphene oxide. These graphene oxides can contain a few layers (less than 10 layers), multiple layers (10-100 layers), or even more layers (greater than 100 layers). These graphene oxides can be reduced to reduced graphene oxide in some cases.
[0090] In some examples, the turbostratic graphene may include heteroatoms. These heteroatoms may include Fe, CO, Ni, Cu, Zn, Al, PD, Pt, Ag, Au, Rh, or one or more other transition metals or one or more main group metals. The heteroatoms may also include B, N, F, Si, P, S, Cl, or one or more other main group elements. The one or more heteroatoms may be single atoms, clusters, or nanoparticles. The one or more heteroatoms may improve the mechanical performance of the turbostratic graphene. The one or more heteroatoms may also induce a non-uniform charge distribution across the turbostratic graphene surface (enhancing graphene-filler and graphene-polymer interactions) or function as promoters or antioxidants.
[0091] In some examples, turbostratic graphene may be functionalized to tune the polarity of the turbostratic graphene. Functionalization may include mechanical milling, hydrothermal or solvothermal treatment, chemical or electrochemical treatment, or any combination thereof.
[0092] In some examples, turbostratic graphene may be functionalized to improve its interaction with fillers in rubber composites, or with rubber polymers, or both. Functionalization may include mechanical milling, hydrothermal or solvethermal treatments, chemical or electrochemical treatments, or any combination thereof.
[0093] In some cases, turbostratic graphene may be functionalized to act as an initiator to start a polymerization reaction.
[0094] In some examples, turbostratic graphene may be functionalized to act as an accelerator or antioxidant for rubber composites.
[0095] Referring again to FIG. 1, at step 104, a second material comprising rubber is provided.
[0096] The rubber material may include rubber latex, such as natural rubber latex, synthetic rubber, rubber-type polymers, or any other similar material.
[0097] In some embodiments, any rubber latex may be used. The rubber latex may include, but is not limited to, styrene-butadiene rubber (SBR), polyisoprene, isoprene / isobutylene rubber, acrylonitrile / butadiene rubber, ethylene / propylene / diene rubber (EPDM), ethylene / propylene rubber (EPM), chlorosulfonated polyethylene (CSM), styrene copolymer, styrene block copolymer, styrene / isoprene / styrene (SIS) rubber, or any combination thereof.
[0098] In some embodiments, the rubber material may be a solid rubber, rubber or solid solution. In some embodiments, the rubber material may be a liquid rubber material. In some embodiments, the liquid rubber material may be dispersed in an organic solvent or a mixture of organic solvents. In some embodiments, the liquid rubber material may be emulsified in water or another fluid.
[0099] At step 106, the first material including turbostratic graphene is mixed with the second material including rubber. In some embodiments, the turbostratic graphene may be mixed by any suitable method, including but not limited to high shear mixing, mechanical stirring, or ultrasonic treatment.
[0100] In step 108, a turbostratic graphene rubber composite is produced.
[0101] Turbostratic graphene rubber composites offer several advantages that enable their use in a number of applications: the mechanical, electrical, thermal and chemical properties of the turbostratic graphene rubber composites may be more favorable than the rubber material alone.
[0102] Compared with conventional graphene rubber composites, turbostratic graphene rubber composites can liberate more favorable material properties. Conventional graphene (Bernal stacking) is hard to exfoliate, contains 15 layers, up to more than 100 layers, and has a Raman peak index 2d / g less than 0.3. Turbostratic graphene can be more easily exfoliated to exfoliate larger portions of graphene into few-layer graphene, thus providing more advantages when applied to rubber composites. Turbostratic graphene further includes properties such as easy exfoliation into ultrathin graphene sheets (1-10 layers), high purity (>99%), high Raman peak index 2d / g (0.3-1.1), and a wide range of adjustable lateral size (5 nm-2 μm), which contribute to the desirable material properties of turbostratic graphene rubber composites. Furthermore, the weakened interlayer interactions of turbostratic graphene allow it to be easily dispersed in solution and more uniformly mixed into the rubber matrix when producing graphene-rubber composites, allowing for a much lower graphene concentration to achieve the same performance enhancement when compared to the difficult-to-disperse thick-layer Bernal stacked conventional graphene. The low defect rate and heteroatoms (especially oxygen) allow turbostratic graphene to exhibit chemical vapor deposition graphene-like properties such as high thermal and electrical conductivity, which may increase the thermal or electrical conductivity of graphene-rubber composites produced with turbostratic graphene.
[0103] Turbostratic graphene's low defect and low heteroatom content result in a relatively non-polar graphene surface, allowing it to be well compatible with most rubbers, which have low interfacial energies. Additionally, the ultrathin nature and good dispersibility and miscibility of turbostratic graphene allow for the fabrication of transparent rubber composites. Turbostratic graphene's low defect rate and large lateral size (up to 2 μm) improve the gas and solvent barrier performance of turbostratic graphene-rubber composites.
[0104] The turbostratic graphene rubber composites described herein may be used in any of the following groups including, but not limited to, automobile tires, composites for automobile tires, parts of automobile tires, tires for other vehicles, O-rings, sealing materials, washers, membranes, belts, foam rubber, flooring, roofing, sports materials, footwear, adhesives, gaskets, hoses, gloves, or any combination thereof.
[0105] In some examples of method 100, turbostratic graphene can be used as a filler to make rubber composites with various types of elastomers. In such examples, when graphene or turbostratic graphene is added to a polymer matrix, the large aspect ratio of the turbostratic graphene sheets creates abundant interfaces with the polymer network, enhancing the mechanical properties of the composite, such as strength, toughness, hardness, stiffness, and modulus. Also, the high thermal and electrical conductivity of turbostratic graphene improves the thermal and electrical properties of composites containing turbostratic graphene. The ultrathin 2D turbostratic graphene sheets form an additional gas barrier in the composite, reducing the gas permeation of the bulk composite.
[0106] The property characteristics of turbostratic graphene-rubber composites could be further improved by applying turbostratic graphene with as few layers as possible, high quality (represented by a high 2D / G ratio measured by Raman spectroscopy), few defects, and high carbon purity.
[0107] In one embodiment of the method 100, a graphene-based natural rubber composite is produced by latex-agglomeration. Turbostratic graphene is produced from metallurgical coke in the form of a powder with particle size ranging from a few microns to a few mm. The metallurgical coke is Joule heated to convert the carbon content to turbostratic graphene. The turbostratic graphene can be further reduced by ball milling into a powder. 0.2 g of turbostratic graphene (1.25 phr) is mixed with 26.7 g of natural rubber latex and 0.44 g of sulfur (2.8 phr) in 200 ml of H2O. The mixture is stirred using a high shear mixer until homogeneously mixed. During stirring, the mixture is gradually acidified by dropwise addition of acetic acid demulsifier to allow the turbostratic graphene, sulfur, and natural rubber to agglomerate. The resulting material is neutralized by washing with water, processed into sheets, and cured overnight at 80°C in a vacuum oven.
[0108] In some embodiments, the amount of H2O, if used, may be adjusted according to the viscosity of the mixture.
[0109] In some embodiments, the high concentration turbostratic graphene latex mixture can be used as a masterbatch to mix with more rubber latex to obtain lower concentrations.
[0110] 8, images 602, 604, and 606 are shown illustrating the stability of turbostratic graphene natural rubber latex dispersions with and without centrifugation, according to one embodiment. As shown in image 602, the resulting graphene / natural rubber latex dispersion is very stable. Furthermore, as can be seen in the other images, the dispersion is stable without precipitation after centrifugation at 31 RCF for 5 minutes (image 604) and 277 RCF for 5 minutes (image 606).
[0111] In some embodiments, fillers may be added to the turbostratic graphene-rubber composite to optimize the material properties of the composite. Fillers may include, but are not limited to, carbon black, ZnO, SiO2, or any combination thereof. Other chemicals such as accelerators, antioxidants / antiozonants, or processing additives may also be added to optimize the vulcanization process. Accelerators may include, but are not limited to, N-cyclohexyl-2-benzothiazole sulfenamide (CBS) and 2-mercaptobenzothiazole (MB), N-tert-butyl-benzothiazole sulfonamide (TBBS), diphenyl guanidine (DPG), or any combination thereof. Antioxidants and antiozonants may include, but are not limited to, 4010NA, Nochek 4729A, 6PPD, TMQ, stearic acid, or any combination thereof.
[0112] In some embodiments, surfactants / dispersants may be employed to improve the dispersion of the turbostratic graphene in the rubber, such as sodium dodecyl sulfate (SDS), sodium dodecylbenzenesulfonate (SDBS), lithium dodecyl sulfate (LDS), sodium deoxycholate (DOC), sodium taurodeoxycholate (TDOC), cetyltrimethylammonium bromide (CTAB), tetradecyltrimethylammonium bromide (TTAB), Pluronic F87, polyvinylpyrrolidone (PVP), polyoxyethylene (40) nonylphenyl ether (CO-890), Triton, etc. X-100, Tween 20, Tween 80, Polycarboylate (H14N), Sodium cholate, Tetracyanoquinodimethane (TCNQ), Pyridinium tribromide, N,N'-Dimethyl-2,9-diazaperopyrenenium dication, N,N'-Dimethyl-2,7-diazapyrene, Tetrasodium 1,3,6,8-pyrenetetrasulfonate, 1-Pyrenemethylamine hydrochloride, 1,3,6,8-Pyrenetetrasulfonic acid tetrasodium salt hydrate, 1-Pyrenecarboxylic acid, 1-Aminopyrene, 1-Aminomethylpyrene The amines may include, but are not limited to, 1-pyrene carboxylic acid, 1-pyrene butyric acid, 1-pyrene butanol, 1-pyrene sulfonic acid hydrate, 1-pyrene sulfonic acid sodium salt, 1,3,6,8-pyrene tetrasulfone tetraacid tetrasodium salt, 6,8-dihydroxy-1,3-pyrene disulfonic acid disodium salt, 8-hydroxypyrene-1,3,6-trisulfonic acid trisodium salt, perylene bisimide bolaamphiphile, tetrabutylammonium hydroxide (TBA), 9-anthracene carboxylic acid, or any combination thereof.
[0113] In some embodiments, the surface of the turbostratic graphene is modified with functional groups to improve the interfacial interaction between the turbostratic graphene and the rubber matrix. The functional groups may include, but are not limited to, oxygen, hydroxide, carbonyl, carboxylic acid, ketone, ether, unsaturated carbon, silane, chlorine, bromine, fluorine, or any combination thereof.
[0114] In some embodiments, the surface of the turbostratic graphene may be grafted with polymer chains, alkenes, or alkynes to crosslink the turbostratic graphene with a rubber matrix.
[0115] In some embodiments, turbostratic graphene may include heteroatoms that promote cross-linking of rubber polymers, inhibition of polymer oxidation, or interfacial interactions between the graphene and the rubber matrix.
[0116] In some embodiments, any suitable demulsifier can be used instead of acetic acid.Suitable demulsifiers include, but are not limited to, organic acids, inorganic acids, organic solvents, or any combination thereof.Organic acids can include, but are not limited to, formic acid, oxalic acid, or any combination thereof.Inorganic acids can include HCl.Organic solvents can include methanol, ethanol, isopropanol, acetone, or any combination thereof.
[0117] In one example embodiment of the method 100, a turbostratic graphene-based natural rubber composite may be produced without the addition of S to produce an uncured turbostratic graphene rubber composite. One example embodiment involves mixing 0.2 g of turbostratic graphene (1.25 parts by weight per 100 parts by weight rubber or 1.25 phr) with 26.7 g of natural rubber latex in 200 ml of H2O. The mixture is stirred using a high shear mixer until uniformly dispersed. Under stirring, the dispersion is gradually acidified by dropwise addition of acetic acid demulsifier, allowing for the aggregation of the turbostratic graphene and natural rubber in the solid state. The resulting material is neutralized by washing with water and then dried overnight at 40° C. in a vacuum oven to obtain a solid turbostratic graphene rubber composite mixture. The dried turbostratic graphene / natural rubber composite does not have a crosslinked polymer matrix and is an uncured composite. The uncured composite may be prepared with a graphene concentration of 0.1 to 50 phr. In some embodiments, any latex rubber may be used in place of natural rubber. In some embodiments, surfactants / dispersants may be used to improve the dispersion of graphene. In some embodiments, graphene surface functionalization may be used to improve the graphene-natural rubber interfacial interaction.
[0118] In some embodiments, the uncured turbostratic graphene rubber composite may function as a masterbatch and be mixed with more natural rubber in an internal mixer, such as a Banbury mixer, or an open mixer, such as a two-roll mill, to produce an uncured turbostratic graphene / rubber composite with a lower concentration of turbostratic graphene.
[0119] Referring to Figure 9, images 502, 504, and 506 are shown depicting three example materials. At 506 is shown an uncured 0.75 phr turbostratic graphene natural rubber composite made from dilution of a 1.5 phr masterbatch according to one embodiment. At 504 is shown a turbostratic graphene-natural rubber composite with a graphene concentration of 1.5 phr. At 502 is shown a natural rubber control with no graphene added. The 0.75 phr turbostratic graphene natural rubber composite in image 506 is made by mixing equal amounts of natural rubber and the 1.5 phr turbostratic graphene natural rubber composite masterbatch to create a turbostratic graphene natural rubber composite sheet with a turbostratic graphene content of 0.75 phr.
[0120] In some embodiments, the rubber material may include a rubber monomer material. In some embodiments, the method 100 may further include a polymerization process to convert the rubber monomer material into a rubber polymer, which encapsulates the turbostratic graphene.
[0121] In some embodiments, the uncured composite may be mixed with any other suitable rubber, such as, but not limited to, styrene-butadiene rubber (SBR), polyisoprene, isoprene / isobutylene rubber, acrylonitrile / butadiene rubber, ethylene / propylene / diene rubber (EPDM), ethylene / propylene rubber (EPM), chlorosulfonated polyethylene (CSM), styrene copolymers, styrene block copolymers, styrene / isoprene / styrene (SIS) rubber, or any combination thereof. The uncured composite may be mixed in an internal mixer, such as a Banbury mixer, or an open mixer, such as a two-roll mill, to produce the corresponding uncured graphene / mixed rubber composite.
[0122] In some embodiments, the method 100 may include mixing the uncured turbostratic graphene rubber composite with other fillers, such as, but not limited to, carbon black, ZnO, SiO2, or any combination thereof. The uncured turbostratic graphene rubber composite may also be mixed with other chemicals, such as crosslinkers (S), silanes (SI-69), processing additives (Struktol ZB49), accelerators (N-cyclohexyl-2-benzothiazole sulfenamide (CBS) and 2-mercaptobenzothiazole (MB), N-tert-butyl-benzothiazole sulfonamide (TBBS), diphenyl guanidine (DPG)), antioxidants (4010NA, Nochek 4729A, 6PPD, TMQ, stearic acid), or any combination thereof. The uncured composite may be mixed in an internal mixer, such as a Banbury mixer, or an open mixer, such as a two-roll mill. The mixed composite may be cured by heating to a desired temperature.
[0123] In some embodiments, a masterbatch turbostratic graphene rubber latex dispersion may be produced. The method includes mixing 5 g of natural rubber latex and 5 g of H2O with 0.3 g of turbostratic graphene by a high shear mixer. The stability of the turbostratic graphene natural rubber latex may be improved by reducing the water content. The reduction in water content may be achieved by using less water during the mixing stage or by using a vacuum oven to remove some of the water content after mixing. In some embodiments, other rubber latexes may be used instead of natural rubber. In some embodiments, surfactants / dispersants may be used to improve the dispersion of graphene. In some embodiments, graphene surface functionalization may be used to improve graphene-natural rubber interfacial interactions.
[0124] In one example embodiment of method 100, the turbostratic graphene-based natural rubber composite may be produced using a casting method. One example embodiment includes mixing 10 g of natural rubber latex and 1.7 g of H2O with 0.09 g of turbostratic graphene. The mixture is sonicated by ultrasonication until a uniform graphene dispersion is achieved. The mixture is cast into a mold of a desired shape and dried in a vacuum oven to obtain an uncured turbostratic graphene natural rubber composite. The amount of turbostratic graphene may be adjusted to 0.1-10 phr in one example embodiment.
[0125] In some embodiments, any suitable latex rubber may be used in place of natural rubber. In some embodiments, surfactants / dispersants may be used to improve the dispersion of graphene. In some embodiments, graphene surface functionalization may be used to improve graphene-natural rubber interfacial interactions.
[0126] In some embodiments, a commercially available Environmental Technology 787 Casting'Craft Mold Builder and natural latex rubber may be used in the method 100. In some embodiments, the mold builder may contain 60 wt% solid material dispersed in water.
[0127] In some embodiments, the graphene rubber composite may include other fillers, such as, but not limited to, carbon black, ZnO, SiO2. The graphene rubber composite may include other chemicals, which may be added before the ultrasonication step. These other chemicals may include, but are not limited to, crosslinkers (S), silanes (SI-69), processing additives (Struktol ZB49), accelerators (N-cyclohexyl-2-benzothiazole sulfenamide (CBS) and 2-mercaptobenzothiazole (MB), N-tert-butyl-benzothiazole sulfonamide (TBBS), diphenyl guanidine (DPG)), antioxidants (4010NA, Nochek 4729A, 6PPD, TMQ, stearic acid), or any combination thereof. Latices of other rubber compositions may be used in place of natural rubber to prepare the turbostratic graphene rubber composite. Fillers and chemicals may also be added later to the uncured composite using an internal mixer such as a Banbury mixer or an open mixer such as a two-roll mill. The uncured turbostratic graphene rubber composite may also be used as a masterbatch to mix with other rubbers using an internal mixer such as a Banbury mixer or an open mixer such as a two-roll mill. The mixed composite may be cured by heating the composite to the desired cure temperature.
[0128] In one embodiment of the method 100, the graphene-based natural rubber composite may be produced by a dipping method. The method includes mixing 10 g of natural rubber latex and 1.7 g of H2O with 0.09 g of turbostratic graphene. The mixture is sonicated in an ultrasonic processor until a uniform graphene dispersion is achieved. A mold of a desired shape is dipped into the mixture and then removed and dried in a vacuum oven to obtain a molded uncured turbostratic graphene natural rubber composite. The amount of turbostratic graphene may be adjusted to 0.1-50 phr. Any other suitable latex rubber may be used in place of natural rubber. Any other suitable surfactant / dispersant may be used to improve the dispersion of graphene. Graphene surface functionalization may be used to improve the graphene-natural rubber interfacial interaction. Fillers (including but not limited to carbon black, ZnO, SiO2, or any combination thereof) may be added to the mixture. Also, chemicals may be added to the mixture prior to the ultrasonication step. The chemicals include, but are not limited to, crosslinkers (S), silanes (SI-69), processing additives (Struktol ZB49), accelerators (N-cyclohexyl-2-benzothiazole sulfenamide (CBS) and 2-mercaptobenzothiazole (MB), N-tert-butyl-benzothiazole sulfonamide (TBBS), diphenyl guanidine (DPG)), antioxidants (4010NA, Nochek 4729A, 6PPD, TMQ, stearic acid), or any combination thereof. The mixed composite can be cured by heating to a desired temperature.
[0129] In one embodiment of the method 100, the turbostratic graphene-based rubber composite may be produced by a solution suspension mixing method. The method includes dissolving a rubber in a solvent. The rubber may include, but is not limited to, natural rubber (NR), styrene-butadiene rubber (SBR), polyisoprene, isoprene / isobutylene rubber, acrylonitrile / butadiene rubber, ethylene / propylene / diene rubber (EPDM), ethylene / propylene rubber (EPM), chlorosulfonated polyethylene (CSM), styrene copolymer, styrene block copolymer, styrene / isoprene / styrene (SIS) rubber, or any combination thereof. The solvent may include, but is not limited to, xylene, toluene, benzene, hexane, cyclohexane, octane, acetone, or any combination thereof. The method includes mixing the turbostratic graphene with a rubber solution using a mixing method, including but not limited to, sonication, mechanical stirring, or high shear mixing. The uncured composite is then produced by evaporating the solvent in the turbostratic graphene-rubber solution mixture in a vacuum oven. Surfactants / dispersants may be used to improve the dispersion of graphene. Graphene surface functionalization may be used to improve the graphene-natural rubber interfacial interaction. Fillers may be added to the mixture, including but not limited to carbon black, ZnO, SiO2, or any combination thereof. Chemicals may be mixed into the mixture during the mixing step with the turbostratic graphene or may be subsequently blended into the composite using an internal mixer, such as a Banbury mixer, or an open mixer, such as a two-roll mill. The chemicals include, but are not limited to, crosslinkers (S), silanes (SI-69), processing additives (Struktol ZB49), accelerators (N-cyclohexyl-2-benzothiazole sulfenamide (CBS) and 2-mercaptobenzothiazole (MB), N-tert-butyl-benzothiazole sulfonamide (TBBS), diphenyl guanidine (DPG)), antioxidants (4010NA, Nochek 4729A, 6PPD, TMQ, stearic acid), or any combination thereof.The uncured turbostratic graphene rubber composites can also be used as masterbatches and mixed with other rubbers using an internal mixer, such as a Banbury mixer, or an open mixer, such as a two-roll mill. The mixed composites can be cured by heating to the desired temperature.
[0130] In one embodiment of the method 100, the turbostratic graphene-based rubber composite is produced by direct processing. Direct processing involves adding turbostratic graphene directly and melting the rubber in an internal mixer, such as a Banbury mixer. The mixer can disperse the graphene throughout the molten rubber. Fillers can also be added during the mixing process. The method includes passing the processed composite through a twin-roll mill several times to allow for uniform mixing. A crosslinker, such as S, is also added to the twin-roll milling process to allow the composite to be cured.
[0131] In some embodiments, the production of turbostratic graphene rubber composites may be achieved by synthesizing a rubber polymer on the turbostratic graphene surface or on the turbostratic graphene.
[0132] In some embodiments, turbostratic graphene rubber composites are prepared by mixing rubber with a graphene-containing medium. The medium can be oil, organic solvent, or water. A high concentration turbostratic dispersion in a medium can be used as a masterbatch to dilute to a lower concentration by mixing with more medium.
[0133] In some embodiments, the method may include dissolving the rubber in a solvent.
[0134] In some embodiments, the method may include curing the uncured mixture.
[0135] In some embodiments, curing the uncured mixture includes heating the mixture to a desired temperature.
[0136] In some embodiments, the method may include injecting the uncured turbostratic graphene-rubber mixture into a mold.
[0137] Referring to FIG. 10, a bar graph 400 is shown comparing the mechanical properties of natural rubber (NR), conventional graphene with natural rubber (XG / NR), and turbostratic graphene with natural rubber (TG / NR), such as a material that may be produced by method 100, according to one embodiment. Conventional graphene differs from turbostratic graphene in that turbostratic graphene is not AB stacked and contains less than 5 layers of graphene. Concentrations of turbostratic graphene and conventional graphene of 1.25 parts by weight per 100 parts by weight rubber (phr) and 5 phr are shown. The stress required in MPa to stretch the rubber composites to 100% elongation and 200% elongation are shown. Natural rubber without any graphene requires the least stress to stretch to 100% and 200% elongation. Conventional graphene natural rubber composites require more stress to stretch than natural rubber without graphene. Increasing the volume of conventional graphene in natural rubber from 1.25 phr to 5 phr increases the stress required to stretch to 100% and 200% elongation compared to natural rubber alone. The turbostratic graphene natural rubber composites show improved properties over both natural rubber alone and conventional graphene natural rubber composites. At both 1.25 phr and 5 phr, the turbostratic graphene natural rubber composites require more stress to stretch to 100% and 200% elongation than the natural rubber and conventional graphene natural rubber composites.
[0138] 11, a bar graph 500 is shown comparing the thermal conductivity of natural rubber (NR), conventional graphene-containing natural rubber (XG), and natural rubber containing turbostratic graphene (TG), such as may be produced by method 100, according to one embodiment. Both the turbostratic graphene-containing material and conventional graphene-containing material in the example of FIG. 11 have a graphene concentration of 1.25 parts by weight per 100 parts by weight rubber (phr) in the graphene-rubber composite. The conventional graphene-natural rubber composite has a decreased thermal conductivity relative to natural rubber alone. In contrast, the turbostratic graphene-natural rubber composite has an increased thermal conductivity relative to natural rubber alone and the conventional graphene-natural rubber composite.
[0139] Referring to FIG. 12, there is shown an image 702 of dispersion of turbostratic graphene in oil as well as a magnified optical image 704 showing uniform graphene dispersion in HyPrene 2000 according to one embodiment.
[0140] To improve the dispersion of graphene in the rubber matrix, the turbostratic graphene may be pre-dispersed in a high viscosity oil. Such oil may be HyPrene 100, HyPrene 200, HyPrene L2000, or any other suitable mineral oil or bio-oil. Dispersion may be achieved by sonication, or mechanical stirring, or high shear mixing. The concentration of turbostratic graphene dispersed in oil may vary from 0.1 wt% to 50 wt%. A typical turbostratic graphene dispersion in HyPrene oil 100, 500, and 2000 is shown in image 702 of FIG. 12. A typical magnified optical image 704 shows a uniform graphene dispersion in HyPrene 2000 with a turbostratic graphene concentration of 5 wt%. The high concentration of graphene in the turbostratic graphene dispersion may be mixed with additional oil to obtain a diluted dispersion. The internal mixer described above may be used to blend the desired concentration of turbostratic graphene oil dispersion into the molten rubber. The turbostratic graphene oil dispersion at a desired concentration can be blended with rubber and other additives in a tire composite manufacturing process. Graphene surface functionalization can be used to improve the graphene-natural rubber interfacial interaction. Also, coupling agents such as organosilicon (silane) can be added to improve the interaction between the graphene and the rubber matrix. [Table 1]
[0141] With reference to Table 1 above, typical tire tread formulations with various types of added turbostratic graphene are detailed so that performance improvements due to the addition of added turbostratic graphene can be evaluated. The three types of turbostratic graphene are chemically mechanically exfoliated flake metallurgical coke-derived turbostratic graphene (TG1), polyhedral graphene from recycled tire carbon black (TG2), and another polyhedral graphene from high-quality carbon black (TG3). TG1 was first reduced and exfoliated using pyrene as an exfoliant by mechanical milling method. Graphene was first dispersed at 20 wt% in Hyprene L2000 oil. 25 phr of this oil dispersion was then mixed in the formulation to achieve 5 phr of graphene in the rubber composite. The formulations with added turbostratic graphene show increased performance over the control formulation without added turbostratic graphene.
[0142] Referring to Figure 13, a line graph 800 is illustrated comparing the cure behavior of a control 802 (no turbostratic graphene added) and three turbostratic graphene added rubber composites: TG1 804, TG2 806 and TG3 808, measured using a moving die rheometer in accordance with the ASTM D5289 (Standard Test Method for Rubber Property-Vulcanization Using Rotorless Cure Meters) standard, the entire contents of which are incorporated herein by reference. All three turbostratic graphenes accelerated the cure process when added to rubber. The scorch times, which indicate the onset of crosslinking of the polymer, were 1.97 minutes for TG1 804, 1.88 minutes for TG2 806 and 1.82 minutes for TG3 808, which are faster than the 2.17 minutes for the control sample. The T90, considered as the end of the curing process, is 5.67 min for TG1 804, 5.29 min for TG2 806, and 5.2 min for TG3 808, which are also faster than 6.48 min for Control 802. Meanwhile, compared to the control samples, the maximum torque of TG1 804, TG2 806, and TG3 808 is improved by 6%, 9%, and 8%, respectively, indicating that the addition of turbostratic graphene increases the stiffness and hardness of the turbostratic graphene rubber composites with respect to the control.
[0143] Referring to FIG. 14, there is illustrated a line graph 900 comparing the rheological properties of a control 902 (without turbostratic graphene) and three graphene-loaded rubber composites: TG1 904, TG2 906, and TG3 908, as measured using a Mooney Viscometer in accordance with ASTM D1646 (Standard Test Method for Rubber-Viscosity, Stress Relaxation, and Pre-Vulcanization Characteristics (Mooney Viscometer)), the contents of which are incorporated herein by reference in their entirety. The initial viscosity was measured after heating the samples for 1 minute. The viscosity for TG1 904 is 89.82 MU, the viscosity for TG2 906 is 104.11 MU, and the viscosity for TG3 908 is 98.44 MU, which are 8%, 26%, and 19% higher than the control (82.79 MU), respectively. The ML1+4 (after 4 min) for TG1 904, TG2 906, and TG3 908 were 57.15 MU, 63.16 MU, and 62.11 MU, respectively, still 14%, 26%, and 24% higher than the control (50.19 MU), respectively. Therefore, adding graphene to rubber composites can effectively enhance the filler network, improve the filler-filler interaction, and increase the stiffness of the composites. Compared with the flake-like TG1 904, the polyhedral TG2 906 and TG3 908 can provide a more efficient network and result in higher stiffness.
[0144] Referring to FIG. 15, a bar chart 1000 is shown comparing the hardness after cure of a control (no turbostratic graphene) and three graphene-added rubber composites. Testing was performed using a durometer in accordance with ASTM D2240 (Standard Test Method for Rubber Property-Durometer Hardness), the entire contents of which are incorporated herein by reference. Flake TG1 shows a 3% improvement in hardness compared to the control, and polyhedral TG2 shows a 6% improvement in hardness, again indicating that polyhedral graphene provides a more efficient network.
[0145] Referring to Figure 16, a bar chart 1100 is shown comparing the tensile at break of a control 1202 (no turbostratic graphene) and three graphene-loaded rubber composites after curing. Testing was performed according to ASTM D412 (Standard Test Methods for Vulcanized Rubber and Thermoplastic Elastomers-Tension), the entire contents of which are incorporated herein by reference. Flake-like TG1 shows a 9% improvement over the control, while polyhedral TG3 also shows a 6% improvement.
[0146] Referring to FIG. 17, a bar chart 1200 is shown comparing the cured modulus of a control 1202 (no turbostratic graphene) and three graphene-loaded rubber composites, TG1 1204, TG2 1206, and TG3 1208. Modulus was measured at 50%, 100%, 200% and 300% elongation where possible. Testing was performed in accordance with ASTM D412 (Standard Test Methods for Vulcanized Rubber and Thermoplastic Elastomers-Tension), the entire contents of which are incorporated herein by reference. TG samples show at least a 7% improvement in modulus, with TG2 1206 showing up to a 24% improvement at 100% elongation.
[0147] 18A and 18B, a flow chart illustrating a method 200 for making a turbostratic graphene rubber composite is shown. Method 200 includes all of the steps of method 100 and may further include any or all of steps 202, 204, 206, 208, 210, 212, 214, 216, or 218. The steps of method 200 may be in any order. The discussion above with reference to method 100 and the turbostratic graphene rubber composite may also be applied to method 200.
[0148] In step 202, the rubber material is polymerized. In an example of the method 200 that includes step 202, the rubber material may include a rubber monomer.
[0149] In step 204, a surfactant and / or dispersant is added.
[0150] In step 206, a demulsifier is added to the latex mixture.
[0151] In step 208, the turbostratic graphene rubber composite is mixed with another material before being cured.
[0152] In step 210, the turbostratic graphene rubber composite is cured.
[0153] In step 212, the turbostratic graphene is functionalized.
[0154] In step 214, a crosslinking agent, an accelerator, an antioxidant, a filler, or an interfacial functionalizing agent is provided to the turbostratic graphene rubber composite.
[0155] In step 216, the uncured mixture is placed or poured into a mold.
[0156] At step 218, the uncured mixture is cured, including adding a crosslinking agent to the rubber latex.
[0157] 19, a flow chart illustrating a method 300 of manufacturing a polyhedral graphene composite is shown. Method 300 may include steps 302, 304, 306, and 308. The discussion above with reference to methods 100 and 200, and turbostratic graphene rubber composites, may be applied to method 300.
[0158] Polyhedral graphene including a first material is provided in step 302. The polyhedral graphene can be any of the graphenes described above.
[0159] At step 304, a second material is provided. The second material may include a material that may be easily mixed or dispersed with another material. The second material may include, but is not limited to, concrete, cement, epoxy, a coating, asphalt, a plastic, a polymer, a polyurethane foam, rubber, a glass ceramic, a tire material, a tire tread formulation, a tire tread material, or a wood composite material.
[0160] The first material is mixed with the second material in step 306. The polyhedral graphene may be mixed by any suitable method, including but not limited to mechanical stirring or sonication instead of high shear mixing.
[0161] In step 308, a polyhedral graphene composite is produced. The polyhedral graphene composite may include more favorable mechanical, electrical, thermal and chemical properties than the first material alone in some embodiments and configurations.
[0162] Although the above description provides one or more example devices, methods, or systems, it will be understood that other devices, methods, or systems may fall within the scope of the claims as interpreted by one of ordinary skill in the art. For example, combinations of the example embodiments may be within the scope of the claims as interpreted by one of ordinary skill in the art.
Claims
1. Providing a first material comprising turbostratic graphene; Providing a second material comprising rubber; mixing the first material with the second material; preparing a turbostratic graphene rubber composite; A method for producing a composite material comprising the steps of:
2. 10. The method of claim 1, further comprising curing the turbostratic graphene rubber composite.
3. 3. The method of claim 2, further comprising mixing the turbostratic graphene rubber composite with another material before curing.
4. 3. The method of claim 2, wherein the curing process is accelerated by the addition of either a crosslinking agent, an accelerator, or heat.
5. 2. The method of claim 1, wherein the turbostratic graphene comprises flakes or sheets such as graphene and polyhedral graphene.
6. 2. The method of claim 1 , wherein the turbostratic graphene comprises graphene-like flakes or sheets.
7. The method of claim 6, wherein the turbostratic graphene comprises a lateral size of 2 nm to 100 μm.
8. The method of claim 1 , wherein the turbostratic graphene comprises polyhedral graphene.
9. The method of claim 8, wherein the polyhedral graphene has a diameter of 3 nm to 200 nm.
10. 9. The method of claim 8, wherein the polyhedral graphene comprises a plurality of walls, each of the plurality of walls comprising 2 to 100 layers.
11. Providing a first material comprising polyhedral graphene; Providing a second material; mixing the first material with the second material; Producing a polyhedral graphene composite material; A method for producing a composite material comprising the steps of:
12. 12. The method of claim 11, wherein the second material comprises any one or more of rubber, cement, concrete, epoxy, coating, asphalt, plastic, polymer, polyurethane foam, glass ceramic, tire material, tire tread construction, tire tread material, or wood composite material.
13. 12. The method of claim 11, further comprising curing the polyhedral graphene composite.
14. 14. The method of claim 13, further comprising mixing the polyhedral graphene composite with another material before curing.
15. 14. The method of claim 13, wherein the curing process is accelerated by the addition of either a crosslinking agent, an accelerator, or heat.
16. The method of claim 11, wherein the polyhedral graphene has a diameter of 3 nm to 200 nm.
17. 12. The method of claim 11, wherein the polyhedral graphene comprises a plurality of walls, each of the plurality of walls comprising 2 to 100 layers.
18. 12. The method of claim 11, further comprising mixing the rubber with a polyhedral graphene-containing medium, the polyhedral graphene-containing medium comprising any one or more of an oil, an organic solvent, water, or a mixture of solvents.
19. 20. The method of claim 18, further comprising adding a surfactant and / or a dispersant to improve dispersion of the polyhedral graphene in the polyhedral graphene-containing medium.
20. adding an emulsifier to the polyhedral graphene latex mixture; further processing the polyhedral graphene latex mixture to obtain a solid polyhedral graphene composite material; The method of claim 11 further comprising:
